Pengaruh karakteristik individu dan karakteristik organisasi terhadap pengembangan karir pegawai dinas Pertanian Tanaman Pangan dan Hortikultura - Muhammad Ilham; Nabila Hilmy Zhafira (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2023)
Individual characteristics and organizational characteristics are the two variables used in this study to analyze employee career development. The object of research is an employee of the Agriculture, Food Crops and Horticulture Office of West Aceh district. The type of method used is quantitative through data collection using a total sampling technique, namely taking data on the entire population of 56 respondents. Primary data was collected through a questionnaire with a Likert scale and data analysis through the techniques used were validity and reliability tests; classic assumption test, multiple linear regression analysis; t test, F test and the coefficient of determination (R²) with a computer application program tool, namely SPSS. The results of the analysis show that the individual characteristic variable (X1) is negative. This shows that individual characteristics (X1) have no significant effect on the career development variable (Y) and the organizational characteristics variable (X2) shows a positive value. This shows that organizational characteristics have a significant effect on career development variables (Y) and the F test is known to be positive which indicates that individual characteristics variables (X1) and organizational characteristics (X2) have a significant influence simultaneously on career development variables.